VD_FINDINFO HC / 2010 / 644 vom 2. Dezember 2010 - VD Tribunal cantonal (2010)
BAIL À LOYER, DEMEURE DU DÉBITEUR, LOGEMENT, LOYER, RÉSILIATION IMMÉDIATE, EXPULSION DE LOCATAIRE | 257d CC, 457 CPC, 9 Cst., 23 LPEBL